Wisdom Energy: Basic Buddhist Teachings - Lama Yeshe; Zopa Rinpoche; YESHE (Lama); RINPOCHE (Zopa) (New Delhi: Timeless Books, 1994)
Wisdom Energy is a simple and compelling introduction to Buddhism by two Tibetan lamas renowned for their insight and skill in teaching Westerners. Containing an entire meditation course, it goes to the heart of basic Buddhist practice and discusses the meaning and purpose of meditation, the causes of dissatisfaction and unhappiness, and the methods for subduing them and gaining control over our minds and lives. Originally published in 1976, Wisdom Energy still preserves the power, humor, and directness of the lamas's first teaching tour of North America, giving the reader the feeling of an intimate audience with two highly respected teachers.
Keywords: Hinduism; Meditation; Spiritual Practice